Pembagian Harta Waris Menurut Kebiasaan Masyarakat Desa Sanding Marga Perspektif Hukum Waris Islam dan KUHPerdata - Medi Sandira; Siti Rochmiyatun; Yusida Fitriyati (Muqaranah, 2023)
Indonesian people have their own habits regarding the distribution of inheritance, such as those in the Sanding Marga Village community. The people of this village do not carry out inheritance distribution as determined by Islamic law. Thus, this study aims to examine the distribution of inheritance in the Sanding Marga village community in the perspective of Islamic inheritance law and civil law. The problem in this research is how to analyze Islamic inheritance law and civil law on the habit of dividing inheritance in the people of Sanding Marga Village. This research is a field research with locations in Sanding Marga Village. Primary data and secondary data are used together in this study. The data that has been collected was analyzed descriptively qualitatively. The results of the study found that the Sanding Marga village community distributed inheritance in a kinship manner by way of deliberation. Inheritance is divided equally by both women and men. Distribution of inheritance like this is not prohibited in Islamic inheritance law as long as it is done peacefully and does not cause disputes. According to civil law, this is also not prohibited.